Perlindungan Hukum Bagi Kreditur Dalam Hal Debitur Meminjamkan Objek Jaminan Fidusia Kepada Pihak Ketiga : Studi Putusan Nomor 05/Pdt.G/2013/PN Kis. - Denny Imaduddin Akbar; H. Zaenal Arifin Dilaga (Private Law, 2022)
Fiduciary is one of the material guarantees known in Indonesian law. In the fiduciary agreement, goods used as objects of fiduciary security are still under control of the debtor and it cannot be controlled by creditor, so in this case, transfer of ownership without physically. Debtor must have good faith in maintaining the object carefully. The method of this research is normative legal research. The result of this research shows that legal protection for creditor consists of two ways namely preventive legal protection and repressive legal protection. Preventive legal protection is inclusion of prohibition clause for debtors to lend of the object of fiduciary to third party without the approval of creditor. Repressive legal protection where creditor can file a lawsuit to the court according to domicile. In Article 23 of Law No. 42 of 1999 concerning Fiduciary stated that debtor is prohibited from transferring, mortgaging, or leasing to other parties of the object of fiduciary which are not inventory items, except prior written approval from creditor.